In vitro studies on phytochemical analysis and antioxidant activity of citrus maxima (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Citrus fruits are rich source of vitamin-C (Ascorbic acid). In the present study the antioxidant activities of the pulp of some of the citrus fruits has been investigated. The results indicate that the aqueous extracts from citrus fruit pulp contain significant antioxidant activity. In vitro antioxidant activity was determined by various procedures and it has been determined that aqueous, methanol and petroleum ether fraction of pulps of citrus fruits possessed maximum antioxidant activity in reference to standard antioxidant.  The study thus revealed that pulp of Citrus maxima fruits are useful for consumption and are beneficial for health. This study may thus lead to the phytochemical analysis and antioxidant activity of citrus maxima. They can be used as a potent natural antioxidant additive or food products and as a dietary supplement.